Enhancing Postpartum Mothers' Knowledge about Colostrum: Education for Infant Health - Rahman, Abd.; Tarizah, Nurul; Podding, I Takko (Nursing Case Insight Journal, 2025)
The proper administration of colostrum to newborns is crucial for supporting their immune system and preventing various infectious diseases. However, many postpartum mothers still lack understanding of the importance of colostrum, which affects the practice of colostrum feeding. This study aims to describe the improvement in postpartum mothers' knowledge about the importance of colostrum through educational intervention at a hospital. This descriptive research uses a One Group Pre Test-Post Test approach. The study participants consisted of 31 postpartum mothers admitted. Data collection was done using a questionnaire given before and after providing education through leaflets about colostrum. The results showed a significant increase in knowledge after the education, with all respondents (100%) demonstrating good knowledge about colostrum after the intervention. This improved knowledge is expected to encourage postpartum mothers to provide colostrum to their babies, thereby improving their health and immunity